Analisis Pengaruh Beberapa Faktor Terhadap Keputusan Pembelian Air Minum Dalam Kemasan (Amdk) Merek Aqua(Studi pada konsumen AQUA di Kec.Nguter, Sukoharjo) - Winarto, Andy Eko; , Drs.Kusdiyanto,MSi (2017)
This study aims to determine whether there is significant influence price, product quality, and promotion of their product purchasing decisions Bottled Drinking Water Aqua and to find among the variable price, product quality, and the promotion of which variable had a dominant influence on purchasing decisions Bottled Water Aqua. The population in this study is the household consumer products Aqua mineral water in the region Nguter, Sukoharjo. In this study determined the sample size 25 times the independent variable. Multiple regression analysis which will be conducted by three independent variables requires adequencysample of 100 respondents. Sample collection method used was purposive sampling. Data analysis techniques used test instrument, The reliability test, classic assumption test, multiple regression test. Result of this research variable of product quality have the influence which signifikan to purchasing decision. Price variable have the influence which signifikan to purchasing decision. Promotion variable have the influence which signifikan to purchasing decision. variable of product quality (X1), price (X2), promotion (X3) by together to purchasing decision (Y). Result of analysis test the coefficient determinasi obtained Adjusted R square (R2) equal to 0,595, this matter indicate that the variable of product quality (X1), price (X2), promotion (X3) have the influence to variable of purchasing decision equal to 59,5%. While the rest (100 - 59,5 = 40,5%) influenced by other factors outside accurate variable.